Cardiac and Stress Biomarkers and Chronic Kidney Disease Progression: The CRIC Study. (1st November 2019) - Bansal, Nisha; Zelnick, Leila; Shlipak, Michael G; Anderson, Amanda; Christenson, Robert; Deo, Rajat; deFilippi, Christopher; Feldman, Harold; Lash, James; He, Jiang; Kusek, John; Ky, Bonnie; et al.
Abstract: BACKGROUND: Increases in cardiac and stress biomarkers may be associated with loss of kidney function through shared mechanisms involving cardiac and kidney injury. We evaluated the associations of cardiac and stress biomarkers [N-terminal pro-B-type natriuretic peptide (NT-proBNP), high-sensitivity troponin T (hsTnT), growth differentiation factor 15 (GDF-15), soluble ST-2 (sST-2)] with progression of chronic kidney disease (CKD). METHODS: We included 3664 participants with CKD from the Chronic Renal Insufficiency Cohort study. All biomarkers were measured at entry. The primary outcome was CKD progression, defined as progression to end-stage renal disease (ESRD) or 50% decline in estimated glomerular filtration rate (eGFR). Cox models tested the association of each biomarker with CKD progression, adjusting for demographics, site, diabetes, cardiovascular disease, eGFR, urine proteinuria, blood pressure, body mass index, cholesterol, medication use, and mineral metabolism. RESULTS: There were 1221 participants who had CKD progression over a median (interquartile range) follow-up of 5.8 (2.4–8.6) years. GDF-15, but not sST2, was significantly associated with an increased risk of CKD progression [hazard ratios (HRs) are per SD increase in log-transformed biomarker]: GDF-15 (HR, 1.50; 95% CI, 1.35–1.67) and sST2 (HR, 1.07; 95% CI, 0.99–1.14). NT-proBNP and hsTnT were also associated with increased risk of CKD progression, but weaker than GDF-15: NT-proBNP (HR, 1.24; 95% CI, 1.13–1.36) and hsTnT (HR, 1.11; 95% CI, 1.01–1.22). CONCLUSIONS: Increases in GDF-15, NT-proBNP, and hsTnT are associated with greater risk for CKD progression. These biomarkers may inform mechanisms underlying kidney injury.